PENGGUNAAN MEDIA SOSIAL DALAM KEGIATAN PENDIDIKAN PEMUSTAKA (USER EDUCATION) PERPUSTAKAAN IAIN PONOROGO DI ERA NEW NORMAL - Fransisca Puspitasari; Dwi Eliana Sari (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This study aims to describe user education activities in the new normal era. This was motivated by the limitation of face-to-face activities during the new normal period which was then responded by the IAIN Ponorogo library by organize the use of social media in user education activities. This study uses qualitative research with data collection methods is observation, interviews and literature study. The results showed that there were several social media used to promote activities as well as the implementation of user education, such as websites, Instagram, Facebook, Google Form and Youtube to make it easier for students to recognize and utilize library facilities effectively and efficiently. The delivery method used in the implementation of user education activities is through the use of audio-visual uploaded on the Official Youtube of IAIN Ponorogo. The form of activity is directed at library orientation, including introduction to libraries, browsing library collections, borrowing and returning book collection, and procedure uploading student final project.